Whole blood chloroquine concentrations with Plasmodium vivax infection in Irian Jaya, Indonesia. - Baird, J; Leksana, B; Masbar, S; Suradi; Sutanihardja, M; Fryauff, D; Subianto, B (1997)
Whole blood concentrations of self-administered chloroquine (CQ) and its metabolite desethylchloroquine (DCQ) were measured in 168 patients with microscopically confirmed infection by Plasmodium vivax in northeastern Irian Jaya, Indonesia. The study consisted of both survey and passive case detection in four separate villages between 1992 and 1994. The subjects were Javanese people 4-51 years old who had lived in the Arso region for up to two years. The sum of CQ and DCQ ranged from 0 to 8,342 ng/ml of whole blood, and 122 subjects (73%) had > or = 100 ng/ml of CQ plus DCQ, the estimated minimally effective concentration (MEC) in whole blood against chloroquine-sensitive P. vivax. Among 56 subjects reporting to a clinic with symptoms of malaria, 53 (95%) had ordinarily effective levels of chloroquine in blood. Among 109 largely asymptomatic malaria patients found by survey case detection, 69 (63%) had chloroquine blood levels greater than the MEC. Virtually all clinical and most subclinical vivax malaria in this region occurs despite ordinarily effective levels of chloroquine in blood.